Strategic Human Resource Development For Regional Secretary Apparatus Enhancement In The Maros District: An Analytical Study - Indriati Amirullah; Nurmadhani Fitri Suyuti; Khaeriyah Khaeriyah; Steviani Batti (Pusat Riset dan Inovasi Nasional, 2023)
This study discusses human resources development in improving the performance of the regional secretariat apparatus in the Maros Regency. This descriptive research provides an overview and explanation of human resource development strategies to enhance apparatus performance at the Regional Secretariat Office of Maros Regency. The results of the Human Resource Development Strategy research were carried out through 3 steps: employee recruitment, Placement, education, and training (Training). These three steps are well implemented, even though they could be better in that action needs to be taken toward Improvement. And the factors that influence Human Resource Development, namely Leadership, Work Environment, and Budget.